طرق دفع الإشكال عن الآيات القرآنية عند الشيخ أنور شاه الكشميري نماذج من كتابه "مشكلات القرآن (Al Basirah, 2020)
Almighty Allah revealed the Qur'an as an endorsement of the prophethood and guidance for people. Moreover, Allah (S.W.T) ordered to think andponder over the verses of Holy Quran, for example Allah (S.W.T) said in avers: “This is the Blessed Book that we have revealed to you, (O Muhammad),that people with understanding may reflect over its verses and those withunderstanding derive a lesson” [38:29], another verse of holy Quran describes“Do they, then, not reflect on the Qur‟an? Or are there locks on their hearts”[47:24] etc. Many scholars worked extensively interpreting the verses of theHoly Quran due to its importance, as emphasized in the above verses, andcontributed humongous to the literature of Tafseer and Quranic sciences.Some scholars coined the term „abstruse verses of the Holy Quran‟ an areawhere it seems that the Quranic verses and Prophetic sayings areconflicting, or the interpretation of our predecessors doesn‟t match with thecontext of the verse and sometime due to the multiple meanings of a singleword also cause a difficulty for a reader. The literature is so vast in thisarea, thus, it is now considered as a branch of Quranic Sciences: „Theabstruse verses of the Holy Quran‟. Scholars from the subcontinent alsocontributed, and adopted different approaches to elucidate „the abstruse versesof the Holy Quran‟. First book in this field was written by Sheikh Anwar ShahKashmiri with the title of “Mushkilat ul Quran” (The Problems of the Qur‟an)and this book is considered as a primary source in this field, which indicatesits popularity among the scholars of Tafseer & Quranic Sciences insubcontinent. Keeping in mind the importance of this book this article cites theauthor‟s approach to elucidate so called abstruse verses of Holy Quran.
Keywords: Abstruse verses, Mushkilat ul Quran, subcontinent.